SISTEM INFORMASI AKUNTANSI PERSEDIAAN BARANG DAGANG PADA PT TASLY WORLD INDONESIA CABANG BANDUNG - Hery Dwi Yulianto; Sifa Fauziah; Ony Widilestariningtyas (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2012)
PT Tasly World Indonesia Branch Bandung is addressed in Jl. Abdul Rachman Saleh 9 City Square A-3 Bandung. At the time of recording supplies, PT Tasly World Indonesia Branch Bandung is already using the computer by using Microsoft Office Excel 2003, which is often in error recording. On the problems the writer took the title "Accounting Information Systems Inventory Trade at PT Tasly World Indonesia Branch Bandung". Research type which writer applies is base research, data type which writer applies is qualitative data and quantitative data, research design type which writer applies is research design with primary data and secondary data, research method which writer applies is research of eksploratoris and descriptive research, data collecting technique which writer applies is field researcher what consisted of interview and observation and bibliography research system development method which writer applies is methodologies orienting at process, data and output. System development structure applied is Waterfall. Scheme of information system applied is context diagram, data flow diagram, and flowchart With writer makes scheme of trade stock accounting information system, expected data processing, record-keeping of supply data at PT Tasly World Indonesia Cabang Bandung becomes more effective, computerized and efficient as according to financial accounting standard and, output yielded consisted of supply card, supply report, sale report, report retur goods, report retur sale, financial statement, Balance Sheet.